Persepsi Guru Kelas Tentang Efektivitas Kolaborasi dengan Guru Pai dalam Menanamkan Nilai Moderasi Beragama pada Siswa SD N 3 Wanamekar - Nurfadilla Azzahra Plara (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2026)
Collaboration between classroom teachers and Islamic Religious Education (PAI) teachers constitutes an essential strategy for instilling religious moderation values in elementary schools. This study aims to: (1) describe the forms of collaboration developed between classroom teachers and PAI teachers; (2) assess the effectiveness of such collaboration in inculcating religious moderation values; (3) identify changes in students' attitudes as tangible outcomes of collaboration; and (4) analyze supporting and inhibiting factors of collaboration at SDN 3 Wanamekar. A descriptive qualitative approach was applied using field study methods. Data were gathered through in-depth interviews, participatory observation, and document review. Data analysis followed the interactive model of Miles, Huberman, and Saldana, encompassing data condensation, data display, and conclusion drawing. Data credibility was ensured through source triangulation and technique triangulation. Findings indicate that collaboration occurs in two primary forms: reactive collaboration as a spontaneous response to students' intolerant behavior, and planned collaboration involving curriculum coordination, partial co-teaching, and joint evaluation. Collaboration was assessed as sufficiently effective yet suboptimal due to time constraints and excessive administrative burdens. Positive changes in students' tolerance and inclusive attitudes were identified as concrete outcomes. Supporting factors include favorable interpersonal communication, principal support, and moderation value integration in the Merdeka Curriculum. Main inhibiting factors are time limitations, administrative burdens, shallow conceptual understanding of religious moderation, and the absence of a standardized collaboration model. The study recommends establishing structured collaboration schedules and religious moderation training programs for all teachers.